Respostas do tomate cereja irrigado utilizando cobertura do solo com bagana de carnaúba - Rabelo, Janiquelle da Silva (2017)
The tomato compounds a group of vegetables very exigent in water. One alternative for better exploitation of this input occurs through the utilization of efficient irrigation systems, mainly when associated to practice of no-tillage. In light of the above, this work aimed to evaluate the response of tomato under different hydric availabilities without soil, with and without coverage in area located in the Northeastern semiarid. The experiment was conducted in a farmer property designated to commercialization under organic production, belonging to the Program of Education in Cooperative and Student Cells – (Prece), located in the city of Pentecoste-CE. The trial design utilized was a randomized-complete blocks design, within three repetitions per treatment, arranged into a split-plot system. The plots were constituted by irrigation lines with 50; 75; 125 and 150% of evapotranspiration of crop (ETc), which were estimated according to evaporation od Class A Tank and the crop coefficient. On the other hand, the subsections, by no-till coverage by residue of carnauba and soil without coverage, being each plot in a total area of 28m2, being each subsection of 7m2, constituted by 12 plants each. The plant spacing utilized was 0,5m per plant and the row spacing was 1,0 m per line. Within 90 days, it was evaluated the following physiological parameters: a) internal concentration of carbon gas (Ci-ppm); leaf transpiration tax (E-mmol m2s-1); c) stomatal conductance (gs-mol m2s-1); d) liquid photosynthetic tax (A-mmol m2s-1); e) ration between concentration of internal and free carbon gas (Ci/Ca); f) instantaneous efficiency of water use – EiUA (A/E); g) instantaneous carboxylation efficiency (A/Ci); and h) life temperature (°C). It was also evaluated the agronomic aspects related to production and fruits characters, which were harvested with coloration ‘honeydew’, thus evaluated 1) Mass of commercial fruits per plant (g. plant-1); 2) Mass of non-commercial fruits per plant (g. plant-1); 3) Mass of total fruits per plant (g. pant-1); 4) Number of commercial fruits per plant; 5) Number of non-commercial fruits per plant; 6) Total number of fruits per plant; 7) Fruit length (CF, cm); 8) Fruit diameter (DF, cm) and 9) Productivity (PROD, tHA-1). Furthermore, it was also evaluated the efficiency on water use (Kg m3) by cherry tomato plants. The greater numbers of total fruits and commercial ones were obtained while the soil was under coverage of residue of carnauba and concurrently irrigated with lines of 75 and 100% of ETc. The carnauba residue and the lines of 100 and 125% were responsible for the greatest values of fresh matter of fruits. The greater diameters and length of fruits were obtained with soil under coverage. The differences in physiological characteristics have been observed in the plants cropped under different treatments. The maximum productivity, 11404,20 kg ha-1obtained under the line of 140% of ETc. It was verified an efficiency on the water use per plants of cherry tomato of 3,06 kg m3 and 1,95 kg m3 with and without soil coverage, respectively. It has been concluded that it has been possible to obtain greater productivity, efficiency on water use, greater morphological characters and physiological behavior of cherry tomato plants ‘red’ cropped in soil with residue of carnauba and irrigated by drip irrigation comparatively to cropping into soil without coverage.